Physical fitness profile of primary school learners in the Eastern Cape province of South Africa - Howard Gomwe; Lesego Phiri; Chioneso S. Marange (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2024)
Background: Low levels of physical activity in high- to low-income countries, including South Africa, pose a great risk of cardiovascular-related diseases.